Change point analysis and assessment: an integrated methodological design. (1st January 2011) - Mueller, Sabine; Neergaard, Helle; Ulhøi, John P.
The aim of this article is to develop an analytical framework for studying processes such as continuous innovation and business development in high-tech SME clusters that transcends the traditional qualitative-quantitative divide. The article's key contribution is the conceptual integration of four existing and well-recognised but separate approaches to studying events, processes, and change, namely change-point analysis (CPA), event-history analysis (EHA), critical-incident technique (CIT), and sequence analysis (SA) into a single design framework which is especially useful for studying complex and long-term or ongoing processes.